PEMANFAATAN MEDIA INTERAKTIF FROGGY JUMPS UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB SISWA SDI SURYA BUANA MALANG - Septiana, Gita Kartika; Jauhari, Qomi Akit (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the effectiveness of the use of interactive media Froggy Jumps in improving the mastery of Arabic vocabulary in fifth grade students of SD Islam Surya Buana. The media is a digital-based educational game integrated in the Educaplay platform, designed to increase learning engagement and motivation through an interactive approach. The method used was a pseudo-experiment with a pretest-posttest design to measure the difference in achievement of learning outcomes before and after the intervention. Data analysis showed a significant improvement in Arabic vocabulary acquisition after the application of the media, which was reflected in the increase in evaluation scores as well as an increase in learners' active participation during the learning process. The research findings indicate that the use of Froggy Jumps interactive media is more effective than conventional learning methods in improving vocabulary acquisition. This media is proven to be able to motivate learners, increase active engagement, and facilitate vocabulary comprehension and retention through visual, audio, and interactive game features that are in accordance with the characteristics of learners. Therefore, Froggy Jumps interactive media is recommended as an alternative innovative learning media that is effective in supporting the improvement of Arabic vocabulary acquisition at the elementary school level.